2018
DOI: 10.1088/1752-7163/aa95da
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between total serum immunoglobulin E levels, fractional exhaled breath nitric oxide levels and absolute blood eosinophil counts in atopic and non-atopic asthma: a controlled comparative study

Abstract: tIgE levels, FNO and AEC levels are higher in asthma, specifically in the atopic phenotype, as compared to normal. Total serum IgE levels have moderate correlation with FNO and AEC but FNO and AEC are weakly correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…However, high concentrations of exhaled NO are seen in chronic inflammatory diseases, such as asthma, mainly due to type 2 inflammation resulting in increased activation of iNOS. Airway infections, especially rhinovirus, and allergic rhinitis are also related to higher levels of exhaled NO …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high concentrations of exhaled NO are seen in chronic inflammatory diseases, such as asthma, mainly due to type 2 inflammation resulting in increased activation of iNOS. Airway infections, especially rhinovirus, and allergic rhinitis are also related to higher levels of exhaled NO …”
Section: Introductionmentioning
confidence: 99%
“…Airway infections, especially rhinovirus, and allergic rhinitis are also related to higher levels of exhaled NO. 2 The measurement of fractional exhaled NO (F E NO) is a useful, non-invasive method to assist with the diagnosis of asthma and monitor treatment effects. In recent years, F E NO has been used as a marker for eosinophilic airway inflammation and asthma, 3 and to identify steroid responsiveness in individuals with chronic respiratory symptoms caused by airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The association between asthma and blood eosinophils is well known. Some studies reported that there was a positive correlation between FENO and peripheral blood eosinophils in asthma patients 26,27 . However, little is known about this correlation in patients with COPD, and some small-scale studies have shown no significant association 15,24,28 .…”
Section: Discussionmentioning
confidence: 98%
“…5 FE NO can therefore aid asthma diagnosis, and, if correctly applied and interpreted, identify patients at risk of exacerbation. 6 In clinical practice, generalized cut-off values of FE NO have so far been difficult to translate to individual patients due to unknown contribution of factors that influence the FE NO value, such as allergen-specific immunoglobulin E level (IgE), blood eosinophil counts, 7 tobacco smoke exposure, 8 upper airway infection, age and height. 9 The interest of measuring the number of blood eosinophils has increased in recent years since the introduction of anti-interleukin-5 therapy for severe eosinophil asthma.…”
Section: Introductionmentioning
confidence: 99%